Analysis of Human Resources for Health in Malawi : Implementation of WISN Study in Seventy-Five Facilities - Mziray, Elizabeth; Gorgens, Marelize; McCauley, Pamela (World Bank, Washington, DC, 2020)
The health workforce in Malawi, along with other African countries suffered from an acute shortage of its workforce. The Malawi health sector strategic plan (HSSP) 2011-2016 set out key strategies and interventions to support the delivery of an essential health package of services. The human resources for health strategic plan included an HRH capacity development plan that focused on training of registered nurse midwifes, nurse midwife technicians, community midwives and community volunteers. These plans focused on production of health care workers (increasing the quantity) but not on the most efficacious distribution based on disease burden and demand for services. Emergency approaches to replace health workers were instituted to address the shortages of health workers together with the fielding of large numbers of community volunteers and community based health surveillance assistants which could be trained in a short space of time and provide the community essential health package (c-EHP). The Ministry of Health (MoH) is currently developing its next health sector strategic plan, with an expansion of the essential health package and is now challenged with increasing its stock of health workers within the context of declining share of development assistance. The World Bank as part of its support to the government of Malawi (GoM) has instituted a WISN study in seventy-five Health facilities targeting eight priority health cadres. Additionally, a mapping and qualitative study have been undertaken to identify key community cadres undertaking direct health related activities with their communities. The results of this study will provide evidence to inform policy and strategy development particularly in relation to the current work of the MoH on development of the new five-year HSSP and HR strategy.